Literary impressionism and modernist aesthetics - Matz, Jesse (Cambridge, U.K. ;|aNew York Cambridge University Press, 2001)
"Jesse Matz examines the writing of such modernists as Henry James, Joseph Conrad and Virginia Woolf, who used the word "impression" to describe what they wanted their fiction to present. Matz redefines literary Impressionism, focusing on the way that impressions destroy standard perceptual distinctions between thinking and sensing,believing and suspecting. He argues that these writers favored not immediate subjective sense, but rather a mode that would mediate perceptual distinctions. Just as impressions fall somewhere between thought and sense, Impressionist fiction occupies the middle ground between opposite ways of engaging with the world. Reconceiving Impressionist fiction in these terms, this wide-ranging study addresses the problems of perception and representation that occupied the great Modernist writers." --Jacket ".
Includes bibliographical references (pages 250-274) and index.
Keywords: Proust, Marcel -- 1871-1922.; English fiction -- 20th century -- History and criticism; Impressionism in literature; English fiction -- 19th century -- History and criticism